Práticas pedagógicas inclusivas para pessoas com deficiência em artigos científicos nacionais e internacionais - Pereira, Guilherme Willisgnton Tavares (2023)
In educational dynamism, the idea of making the teaching-learning process effective has different aspects, one of its focuses being the possibility of developing a good inclusive pedagogical practice that takes into account all the educational actors who influence this practice and the environment in which the itself is inserted. This work aims to analyze specific inclusive pedagogical practices for people with disabilities in national and international scientific articles from Brazil, Chile and Portugal, and as specific, it aims to list successful inclusive pedagogical practices, aimed at people with disabilities verified in national and international scientific articles. international, which are being held in Brazil, Chile and Portugal; and to contrast the local contextualization of the selected countries with the development of their inclusive pedagogical practices. The fulfillment of the proposed objectives is carried out from the methodological process of bibliographical research, following a qualitative approach, focusing on descriptive research, using, for this, the publication of articles indexed in the Scopus and REDIB databases, researched between the years 2015 and 2021, which have objectives aimed at describing or discussing inclusive pedagogical practices developed in Brazil, Chile and Portugal. For the analysis process, the Content Analysis criteria proposed by Laurence Bardin were used as a fundamental instrument. From this, a number of fourteen papers were analyzed through ten themes defined through the article codification process, which were directed to deal with the teaching practice, the relationships between professors, students and the multidisciplinary team, the use of differentiated didactic-pedagogical resources and the selection of techniques and strategies used for the development of practice. In addition to these, the themes also focused on the importance of planning, student autonomy and the adaptation of teaching activities, all discussed based on the influence of public policies in each country on the development of such pedagogical practices. With this, it was noticed that each theme approached and discussed has its individuais importance, at the same time that for an inclusive pedagogical practice to be considered successful, the relationship between the different themes is necessary, together with the context in which such practices occurred. In addition, the culture of each country helps with the understanding of what should be considered a successful inclusive pedagogical practice, and what specific changes are necessary for the effectiveness of the teaching-learning process of students with disabilities. Therefore, one sees the importance of the relationship between the different topics discussed and analyzed here based on scientific articles from different countries, plus the inclusive process of each one of them, so that a practice is considered a good inclusive pedagogical practice.